Individual and combined effect of suboccipital muscle inhibition technique and doming of diaphragm technique for hamstring tightness - Dr. NILAM DAVE; Prof. TUSHAR J.PALEKAR; Dr. SOUMIK BASU (International Journal of Pharma and Bio Sciences, 2017)
Hamstring muscles have the ability to generate high forces rapidly through their eccentric and concentric contractions because of type 2 muscle fibers in them. Decreased hamstring flexibility is a risk factor for the development of patella tendinopathy and patellofemoral pain, hamstring strain injury, and muscle damage following eccentric exercise. A lack of hamstring extensibility is thought to induce changes in lumbopelvic rhythm. 45 subjects with hamstring tightness were selected and randomly divided into three groups: Group A (Suboccipital Muscle Inhibition technique), Group B (Doming of Diaphragm technique) and Group C (both techniques), by lottery method. Each patient was assessed before and immediately after the treatment using Popliteal Angle Test, Sit and Reach Test and Straight Leg Raise. Each patient received 15mins of treatment. At the end of the study, Group C (Suboccipital muscle inhibition and doming of diaphragm technique) showed better result than Group A and Group B.